GPR35 antagonist CID-2745687 attenuates anchorage-independent cell growth by inhibiting YAP/TAZ activity in colorectal cancer cells - Otkur, Wuxiyar; Liu, Xiaolong; Chen, Huan; Li, Siyi; Ling, Ting; Lin, Hanchen; Yang, Renyu; Xia, Tian; Qi, Huan; Piao, Hai-Long (Frontiers in Pharmacology, 2023)
Background and purpose: GPR35, a member of the orphan G-protein-coupled receptor, was recently implicated in colorectal cancer (CRC). However, whether targeting GPR35 by antagonists can inhibit its pro-cancer role has yet to be answered. Experimental approach: We applied antagonist CID-2745687 (CID) in established GPR35 overexpressing and knock-down CRC cell lines to understand its anti-cell proliferation property and the underlying mechanism. Key results: Although GPR35 did not promote cell proliferation in 2D conditions, it promoted anchorage-independent growth in soft-agar, which was reduced by GPR35 knock-down and CID treatment. Furthermore, YAP/TAZ target genes were expressed relatively higher in GPR35 overexpressed cells and lower in GPR35 knock-down cells. YAP/TAZ activity is required for anchorage-independent growth of CRC cells. By detecting YAP/TAZ target genes, performing TEAD4 luciferase reporter assay, and examining YAP phosphorylation and TAZ protein expression level, we found YAP/TAZ activity is positively correlated to GPR35 expression level, which CID disrupted in GPR35 overexpressed cells, but not in GPR35 knock-down cells. Intriguingly, GPR35 agonists did not promote YAP/TAZ activity but ameliorated CID’s inhibitory effect; GPR35-promoted YAP/TAZ activity was only partly attenuated by ROCK1/2 inhibitor. Conclusion and implications: GPR35 promoted YAP/TAZ activity partly through Rho-GTPase with its agonist-independent constitutive activity, and CID exhibited its inhibitory effect. GPR35 antagonists are promising anti-cancer agents that target hyperactivation and overexpression of YAP/TAZ in CRC.